IMMU-19. TARGETING GLIOBLASTOMA IMMUNOSUPPRESSION AND TREATMENT RESISTANCE WITH IBRUTINIB IN COMBINATION WITH STEREOTACTIC RADIATION AND IMMUNE CHECKPOINT BLOCKADE. (9th November 2020) - Ghose, Jayeeta; Raychaudhuri, Baisakhi; Liu, Kevin; Jiang, William; Gulati, Pooja; Liu, Joseph; Rajappa, Prajwal; Ahluwalia, Manmeet; Jacob, Naduparambil; Chakravarti, Arnab; Carson, William; Raval, Raju
Abstract: BACKGROUND: Glioblastoma (GBM) is associated with systemic and intratumoral immunosuppression. Part of this immunosuppression is mediated by myeloid derived suppressor cells (MDSCs). Preclinical evidence shows that ibrutinib, a tyrosine kinase inhibitor FDA approved for use in chronic lymphocytic leukemia and known to be CNS penetrant, can decrease MDSC generation and function. Also, focal radiation therapy (RT) synergizes with anti-PD-1 therapy in mouse GBM models. Thus, we aimed to test the combination of these approaches on immune activation and survival in a preclinical immune-intact GBM mouse model. METHODS: C57BL/6 mice intracranially implanted with the murine glioma cell line GL261-Luc2 were divided into 8 groups consisting of treatments with ibrutinib, RT (10 Gy SRS), or anti-PD-1 individually or in each combination (along with a no treatment control group). Immune cell subset changes (flow-cytometry) and animal survival (Kaplan-Meier) were assessed (n=10 mice per group). RESULTS: Median survival of the following groups including control (28 days), ibrutinib (27 days), RT (30 days) or anti-PD-1 (32 days) showed no significant differences. However, a significant improvement in median survival was seen in mice given combinations of ibrutinib+RT (35 days), ibrutinib+anti-PD-1 (38 days), and triple therapy with ibrutinib+RT+anti-PD-1 (48 days, p < 0.05) compared to controls or single treatment groups. The reproducible survival benefit of triple combination therapy was abrogated in the setting of CD4 + and CD8 + T cell depletion. Contralateral intracranial tumor re-challenge in long-term surviving mice suggested generation of tumor-specific immune memory responses. The immune profile of the tumor microenvironment (TME) showed increased cytotoxic CD8 + T cells and decreased MDSCs and regulatory T cells in the triple combination therapy mice compared to controls. CONCLUSION: The combination of ibrutinib, focal RT, and anti-PD-1 immune checkpoint blockade led to a significant survival benefit compared to controls in a preclinical model of GBM.